Online marketing of self-published e-books : A personal touch for a global audience - Määttä, Tuuli (My University, 2018)
Globalization and digitalization have transformed the way we do business. In the book industry, the effect has been two-fold. Firstly, the emergence of electronic books, e-books, has reduced the costs of producing and distributing books has fallen dramatically, and secondly, self-publishing now enables authors to circumvent publishing houses and market directly to their target audience. However, the change brought on by globalization and digitalization has not yet been as extreme as it has been in other media industries, such as the movie industry or the music industry. The self-published e-book revolution has not taken place despite the fact that the technological advancements are already in place. Therefore, the question becomes: “Is there a marketing problem in the self-published e-book market?” This is a question that has not yet been answered. This thesis examines the online marketing of self-published e-books by first going over the related academic literature and then conducting an empirical study, using netnography as methodology. Currently, according to academic literature, online marketing of self-published e-books is or should be based on reaching niche markets that are scattered globally and engaging in dialogue with the reader. These points are emphasized in the empirical study. According to the study, self-published authors often struggle with marketing due to the fact that writing a book and marketing it require entirely different skill sets. In addition, there is often a core competence issue with self-published e-books. They are published without the help and backing of a publishing house that, to traditionally published authors, offers professional editing and other competitive advantages. Self-published e-books are therefore often perceived as low-quality. The literature suggests that reaching a global niche market is important for the self-published e-book author, but in the empirical study, this proves to be very difficult, especially as many authors have a very limited marketing budget. In this sense, many of the advantages of self-publishing e-books turn out to also be the disadvantages. Because publishing and distribution of e-books is inexpensive, there are many authors who cannot afford marketing. And because self-publishing sidesteps all gatekeepers, it means that books are written and marketed without the professional know-how needed to reach a global niche audience. While in the related literature, community of authors and readers, including dialogue, is seen as paramount, there is little evidence of it in the empirical study. A more obvious community is one that only the authors share. However, this does suggest that perhaps some of the issues self-published authors face today may be solved in the future through author collaboration. The thesis also shows that there is potential in the self-published e-book market, but without further innovation, it lies stagnant.